SOBRE DESENHO, MEMÓRIA E APRENDIZAGEM: uma abordagem neurocientífica visando a educação inclusiva (Revista Apotheke, 2017)
This is an essay on memory and its place in human learning. The theoretical foundations are organized from current authors, doctors and psychologists working in the vast ﬁeld of neuroscience. Children's drawings are presented as an object of research and reﬂection, as well as the graphic schemes that this production provides and the way of making the pictograms that Piekas and I (2013) suggest for the teaching of children with special learning needs.
Keywords: Learning; Memory; Drawings; Children's drawings; Inclusive education